An Authenticated Investigation of Al-Kafawi's postcript on Al-Jurjani's on Eigi's Explanation of Ibn Al-Hajib's Manuscript Mukhtasar Muntaha Assu'aal" - Al-Omari, Faten Ali Ahmed; Buwizan, Mariam Atiyya (Journal of Arts, 2022)
The purpose of the present study is to investigate, localize and authenticate the manuscript of Al-Kafawi on Al-Jurjani's on Eigi's Explanation of Ibn Al-Hajib's Mukhtasar Muntaha Assu'aal", adopting established methods of investigated historical writings and their writer's identification. The manuscript author addressed issues ranging from limits and boundaries, evidence positive or negative and logical measurement. The study is organized into two sections. The first section investigates the era of Kafawi and Jurjani and their postscripts on the manuscript. The second section authenticates Asa'd Afandi manuscript. The study revealed that Kafawi's method was more valid in terms of controversial debating whereby questions were pit forward and answered and where certain statements and quotes were criticized, doubted and approved. The end result of this manuscript can contribute the increase scholrs understanding in fundamental issues of jurisprudence.